2019
DOI: 10.1126/scitranslmed.aav3523
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of short-course antiwolbachial quinazolines for elimination of filarial worm infections

Abstract: Parasitic filarial nematodes cause debilitating infections in people in resource-limited countries. A clinically validated approach to eliminating worms uses a 4- to 6-week course of doxycycline that targets Wolbachia, a bacterial endosymbiont required for worm viability and reproduction. However, the prolonged length of therapy and contraindication in children and pregnant women have slowed adoption of this treatment. Here, we describe discovery and optimization of quinazolines CBR417 and CBR490 that, with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 66 publications
4
52
0
Order By: Relevance
“…Thus, the L . sigmodontis rodent model was chosen by the Bill & Melinda Gates Foundation for the “Macrofilaricidal Drug Accelerator Program” to identify new compounds with a macrofilaricidal effect [ 17 , 23 25 , 54 , 55 ]. Despite this, all filarial rodent models have a shorter filarial life-span in comparison to human pathogenic filariae and differences in the location of the parasites and the associated accessibility of the drug to the filariae (thoracic cavity for L .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the L . sigmodontis rodent model was chosen by the Bill & Melinda Gates Foundation for the “Macrofilaricidal Drug Accelerator Program” to identify new compounds with a macrofilaricidal effect [ 17 , 23 25 , 54 , 55 ]. Despite this, all filarial rodent models have a shorter filarial life-span in comparison to human pathogenic filariae and differences in the location of the parasites and the associated accessibility of the drug to the filariae (thoracic cavity for L .…”
Section: Discussionmentioning
confidence: 99%
“…The L . sigmodontis rodent model has been used to validate macrofilaricidal drug candidates by a consortium led by the Bill & Melinda Gates Foundation, Drugs for Neglected Diseases initiative (DND i ), academia, and pharmaceutical companies and has supported the advancement of a few macrofilaricidal compounds through preclinical and clinical development [ 17 , 22 28 ]. In this study we demonstrate that oxfendazole exhibits excellent macrofilaricidal efficacy following both oral and sc administrations in the L .…”
Section: Introductionmentioning
confidence: 99%
“…Wolbachia titers were reduced by >95% in female worms from rifampicin treated animals at the 1-week timepoint compared to those of worms from vehicle animals. The extensive reduction of Wolbachia titers in adult worms has been previously described in other rodent studies with filarial worms, but the studies were terminated 16-18 weeks post-treatment [26,27,29,40,50], and the long-term effects of antibiotic treatment on filarial worms and their Wolbachia were not evaluated in these models.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have recently shown that short courses of 7-and 14-days of anti-Wolbachia compounds hold promise as excellent drugs to treat onchocerciasis and LF [25][26][27][28][29]. Studies by Hübner et al however, showed that suboptimal treatment regimens of doxycycline in the Litomosoides sigmodontis infection model did not lead to a sustained reduction in Wolbachia loads in worms 14-18 weeks post-treatment and that longer term studies were needed to assess permanent sterilization of female adult worms [27,29].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, an impact of anti-Wolbachia drug candidates on adult worm burden and microfilariae counts is often not observed due to the slow macrofilaricidal efficacy of anti-Wolbachia compounds and the fact that only~50% of mice develop microfilaremia [35], which is also seen in human lymphatic filariasis [36]. Nevertheless, the L. sigmodontis mouse model is very sensitive to short-course treatments and has repeatedly proven valuable for the screening of potential drug candidates against Wolbachia endosymbionts [24,[37][38][39] and provided the basis for the successful human clinical trials with doxycycline. Even though no macrofilaricidal effect was observed for the tested drugs, human clinical studies demonstrated that doxycycline provides a macrofilaricidal effect in human onchocerciasis patients only after 21-27 months following treatment [40].…”
Section: Fig 3 An11251 and Doxycycline Combination Therapy Provides mentioning
confidence: 99%